2019
DOI: 10.1371/journal.pone.0217784
|View full text |Cite
|
Sign up to set email alerts
|

Home range variation and site fidelity of Bornean southern gibbons [Hylobates albibarbis] from 2010-2018

Abstract: Gibbons are highly territorial and have two key areas within these territories. The core area in which we find all sleeping trees and the trees from which the gibbons duet and the wider home range (HR) which has varying levels of overlap with neighbouring gibbon groups. The core area is strenously defended, with the wider HR being more of a shared area for neighbouring groups. We present ranging and movement data on four wild gibbon groups from January 2010 to July 2018. Global Positioning System (GPS) data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Animals are known to exhibit distinct personality traits, or behavioral syndromes, where certain individuals are more bold or aggressive than others 52,53 , and it seems likely that certain gibbon individuals or pairs call more often than others, which would also lead to spatial variation in gibbon calling events. Previous reports of home range size of two gibbon pairs in our population were about 0.34 km 2,54 , but home range size can vary widely even within the same population 55 , making it difficult to know precisely how many pairs were included in the present study. Based on conservative estimates of gibbon home range size (0.3-0.5 km 2 ) it seems likely that at least 6-10 pairs were recorded in our 3 km 2 study area.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Animals are known to exhibit distinct personality traits, or behavioral syndromes, where certain individuals are more bold or aggressive than others 52,53 , and it seems likely that certain gibbon individuals or pairs call more often than others, which would also lead to spatial variation in gibbon calling events. Previous reports of home range size of two gibbon pairs in our population were about 0.34 km 2,54 , but home range size can vary widely even within the same population 55 , making it difficult to know precisely how many pairs were included in the present study. Based on conservative estimates of gibbon home range size (0.3-0.5 km 2 ) it seems likely that at least 6-10 pairs were recorded in our 3 km 2 study area.…”
Section: Discussionmentioning
confidence: 91%
“…For example, early field trials indicated that the maximum gibbon recording distance on our recorders and in this environment was 350-400 m, but calls detected at >400 meters were of very low-quality (<10 SNR) and difficult to distinguish using aural and visual means, which means that there was a low possibility of recording the same calls on multiple recorders. Home range size for two gibbon groups in our population was previously estimated to be 34 ha (0.34 km 2 ), but home range size in gibbons has been shown to be highly variable even within populations 55 , so this may not be representative of the gibbons included in our study. But, given the high degree of territoriality in gibbons 16 , and their relatively small home range size relative to grid spacing of the autonomous recorders, the possibility of re-recording the same vocalizing pair on different recorders in the present study was minimal.…”
Section: Discussionmentioning
confidence: 93%
“…Early field tests indicate that detection distance of calling gibbons is approximately 400 m[75] using our recording settings. We considered high-quality recordings taken from each recorder as a different male based on the territorial nature of gibbons, the documented territory size in other gibbon species[76][77][78] and estimated detection distance of our recorders[75]; see Clink et al[72] for more details.…”
mentioning
confidence: 99%
“…Habitat loss or degradation may leave survivors with smaller HR, lower-quality HR, or both. In the only other study of gibbons in fire-affected habitat, HR locations for three neighboring groups of Bornean southern gibbons (H. albibarbis) remained stable before and three years after a fire, although habitat within one HR was damaged and was no longer used (Cheyne et al, 2019). Similarly, 2000Similarly, -2002Similarly, , 2007Similarly, -2009Similarly, , and 2014, and for this project in 2014-2015 (Table 1).…”
Section: Effects Of 1997 Fire On Habitat Quality In Wcramentioning
confidence: 74%